Multiple socioeconomic risks and cognitive impairment among older men and women in India - T. Muhammad; Manacy Pai; Manish Kumar; T.V. Sekher (Elsevier, 2023)
Introduction: Socioeconomic status (SES) is negatively associated with innumerable health outcomes, including cognitive functioning. Yet much remains undiscovered about SES patterns in later-life cognition in low-and middle-income countries (LMICs). The purpose of this study was to examine the association between separate and combined socioconomic risks and cognitive impairment among older adults in India. Further, given gender disparities in later life cognitive functioning and SES, the study examines the associations between socioeconomic risks and cognitive impairment separately, for older men and women. Methods: Data come from the 2017-18, first wave of the Longitudinal Aging Study in India (LASI), with 31,464 older adults aged 60 years and above. Cognitive impairment was assessed using multiple broad measures of memory, orientation, arithmetic function, and visuo-spatial construction skills. We present descriptive statistics along with cross-tabulation of the outcome variable. Additionally, binary logistic regression analysis was used to test the association between outcome and explanatory variables. SES is measured using education, paid work status, and household wealth measured using monthly per-capita consumption expenditure (MPCE). Results: A proportion of 7.14% of the older men and 20.03% of older women reported cognitive impairment. The odds of cognitive impairment were higher among uneducated older men and women, and older men and women in lowest wealth quintile. Surprisingly, older women without current or prior work history report lower odds of cognitive impairment compared to their peers in labor force. While odds of cognitive impairment are higher among non-working older men, this association is not statistically significant. In older men, the odds of cognitive impairment were 5.34, 7.14, and 13.05 times higher with one, two, and three risk factors, respectively, compared with those with no risk exposure. A similar trend was observed for women but with comparatively lower odds. Conclusions: Our findings underscore the need to distinguish between varying elements of SES to construct "upstream" health policies and programs that redistribute resources. In particular, the findings support the use of multiple SES indicators in identifying older adults most susceptible to cognitive deficits, and planning gender-based interventions to improve cognitive health in late life.